2022
DOI: 10.1021/acsami.1c22439
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Hypericin with SARS-CoV-2 Reveals a Multimodal Antiviral Activity

Abstract: Hypericin is a photosensitizing drug that is active against membrane-enveloped viruses and therefore constitutes a promising candidate for the treatment of SARS-CoV-2 infections. The antiviral efficacy of hypericin is largely determined by its affinity toward viral components and by the number of active molecules loaded on single viruses. Here we use an experimental approach to follow the interaction of hypericin with SARS-CoV-2, and we evaluate its antiviral efficacy, both in the dark and upon photoactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Here, it is conceivable that an oxidative modification, e.g., of theSARS-CoV-2 spike protein, occurs comparably quickly and might therefore inhibit receptor recognition and the cell membrane fusion process [35] Consistent with this idea, it was reported that the high susceptibility of viruses to PDI is not only caused by reduced structural integrity of viral RNA and virion membranes, but by loss of their surface glycoproteins, leading to non-infectious "bald" virions [18]. Since SARS-CoV-2 requires an envelope homotrimeric spike glycoprotein (S) to interact with the cellular receptor ACE-2 [36], it was proposed that selective impairment of surface proteins, like spike glycoprotein (S), by PDI can effectively inhibit infectivity of SARS-CoV-2 [24,25,37]. Additionally, it was suggested that effectivity of antiviral PDI may, in part, be explained by a light-induced photocleavage reaction of viral ssRNA [38].…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is conceivable that an oxidative modification, e.g., of theSARS-CoV-2 spike protein, occurs comparably quickly and might therefore inhibit receptor recognition and the cell membrane fusion process [35] Consistent with this idea, it was reported that the high susceptibility of viruses to PDI is not only caused by reduced structural integrity of viral RNA and virion membranes, but by loss of their surface glycoproteins, leading to non-infectious "bald" virions [18]. Since SARS-CoV-2 requires an envelope homotrimeric spike glycoprotein (S) to interact with the cellular receptor ACE-2 [36], it was proposed that selective impairment of surface proteins, like spike glycoprotein (S), by PDI can effectively inhibit infectivity of SARS-CoV-2 [24,25,37]. Additionally, it was suggested that effectivity of antiviral PDI may, in part, be explained by a light-induced photocleavage reaction of viral ssRNA [38].…”
Section: Discussionmentioning
confidence: 99%
“…It can induce photo-cytotoxicity [64] and has been touted as a potential treatment and detection of cancer [63]. The photosensitising effects of hypericin has also shown efficacy of it being a multimodal antiviral [65], and has been long-known to inactivate murine cytomegalovirus (MCCV) and HIV-1, especially with exposure to fluorescent light [66].…”
Section: Discussionmentioning
confidence: 99%
“…It can induce photo-cytotoxicity [64] and has been touted as a potential treatment and detection of cancer [63]. The photosensitising effects of hypericin has also shown efficacy of it being a multimodal antiviral [65], and has been long-known to inactivate murine cytomegalovirus (MCCV) and HIV-1, especially with exposure to fluorescent light [66]. However, the use of St. John's Wort, by extension hypericin, in combination with other medicines, has previously proven an antagonistic effect [67] and could interfere with contraceptives [68].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies provided evidence that Hyp exhibits potent antiviral activity when against SARS-CoV-2 (Islam et al, 2021;Mohamed et al, 2022). Besides its potent affinity for viral envelope (Delcanale et al, 2022) involves Mpro, RdRp, and 3Clpro (Mahmoudi et al, 2021;Matos et al, 2022).…”
Section: Against Virusesmentioning
confidence: 99%
“…Several studies provided evidence that Hyp exhibits potent antiviral activity when against SARS‐CoV‐2 (Islam et al, 2021; Mohamed et al, 2022). Besides its potent affinity for viral envelope (Delcanale et al, 2022), both Rocha et al and Mahmoudi et al indicated that Hyp could inhibit some specific viral proteins related to many distinct stages of the virus replication cycle in vitro, which involves Mpro, RdRp, and 3Clpro (Mahmoudi et al, 2021; Matos et al, 2022).…”
Section: Pharmacological Effects Of Hypericinmentioning
confidence: 99%